2019
DOI: 10.1177/1558944719873150
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Digit Replantation Following Traumatic Amputation: Nationwide Analysis of Patient Selection, Outcomes, and Cost

Abstract: Background: Indications for replantation following traumatic digit amputations are more liberal in the pediatric population than in adults, but delineation of patient selection within pediatrics and their outcomes have yet to be elucidated. This study uses a national pediatric database to evaluate patient characteristics and injury patterns involved in replantation and their outcomes. Methods: The Healthcare Cost and Utilization Project Kid’s Inpatient Database was queried for traumatic amputations of the thum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…All studies included in this review concluded that following finger amputation, the odds of replantation attempt and replantation success are significantly less for uninsured patients compared with those with private insurance. 17,[20][21][22][23] In addition, having noncommercial insurance was associated with increased odds of amputation following burn injury. 24 Insurance status has been demonstrated to affect the type of skin graft one will receive following hand burns.…”
Section: Patient-related Barriersmentioning
confidence: 99%
“…All studies included in this review concluded that following finger amputation, the odds of replantation attempt and replantation success are significantly less for uninsured patients compared with those with private insurance. 17,[20][21][22][23] In addition, having noncommercial insurance was associated with increased odds of amputation following burn injury. 24 Insurance status has been demonstrated to affect the type of skin graft one will receive following hand burns.…”
Section: Patient-related Barriersmentioning
confidence: 99%
“…While revision amputation is less costly and less complex, replantation is still an important treatment for patients with traumatic digit amputation, in that it can partially restore the function and appearance of the affected finger 3 . However, this sophisticated surgery requires highly experienced hand surgeons and patients require long or extended hospitalization after surgery 9 , 10 . Owing to microsurgical advancements, the success rate of digit replantation reached more than 80% 11 13 .…”
Section: Introductionmentioning
confidence: 99%